Clinical outcomes following shock team implementation for cardiogenic shock: a systematic review - Mohamed Abdelnabi; Ahmed Saad Elsaeidy; Aya Moustafa Aboutaleb; Amit Johanis; Ahmed K. Ghanem; Hazem Rezq; Basel Abdelazeem (The Egyptian Heart Journal)
Abstract Background Cardiogenic shock is a critical cardiac condition characterized by low cardiac output leading to end-organ hypoperfusion and associated with high in-hospital mortality rates. It can manifest following acute myocardial infarction or acute exacerbation of chronic heart failure. Despite advancements, mortality rates remain elevated, prompting interest in multidisciplinary approaches to improve outcomes. This manuscript presents a review focused on the concept of a cardiogenic shock team and its potential impact on patient management and outcomes. Methods A comprehensive search was performed on March 19, 2023, covering PubMed, Web of Science, Scopus, Embase, and Cochrane Library. We included primary studies (prospective and retrospective) only and evaluated their quality using the Newcastle–Ottawa Quality Scale. This review was registered in PROSPERO (CRD42023440354). Results Six relevant studies with 2066 cardiogenic shock patients were included, of which 1071 were managed by shock teams and 995 received standard care. Findings from the reviewed studies indicated the favorable outcomes associated with implementing cardiogenic shock teams. Patients managed by these teams exhibited higher 30-day and in-hospital survival rates compared to those without team intervention. The implementation of cardiogenic shock teams was linked to reduced in-hospital and intensive care unit mortality rates. Additionally, shock team involvement was associated with shorter door-to-balloon times. Conclusion The findings suggest that cardiogenic shock teams play a crucial role in improving patient outcomes through earlier detection and timely interventions. Despite challenges in team implementation, their potential to reduce mortality and improve efficiency in patient care warrants further research and greater integration of multidisciplinary strategies into clinical practice.